2020
DOI: 10.1186/s41983-020-00166-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of nerve ultrasound versus electrophysiological studies in the evaluation of nerve injuries

Abstract: Background: High-resolution ultrasonography (US) is a non-invasive, readily applicable imaging modality capable of depicting real-time static and dynamic information concerning the peripheral nerves and their surrounding tissues. Although electrophysiological studies are the gold standard in the evaluation of nerve injuries, US can be used also to evaluate the morphological changes of nerve injuries. Objectives: To evaluate the role of the high-resolution US in the assessment of nerve injuries and to compare i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…We found a statistically significant difference between diagnosis of the severity of nerve injury by EDX and continuity of the nerve by US at one and three months after repair. This agreed with the study done by Elfayoumy N, et al, (2020) [21] in which they studied 12 nerves diagnosed as complete nerve injuries with the use of EDX, but using US, only three nerves showed fascicular continuity. Lauretti L, et al, [22] found that complete anatomical nerve interruption is easily recognized by the US, while internal nerve damage with the epineurium in continuity is more difficult to interpret.…”
Section: Discussionsupporting
confidence: 91%
“…We found a statistically significant difference between diagnosis of the severity of nerve injury by EDX and continuity of the nerve by US at one and three months after repair. This agreed with the study done by Elfayoumy N, et al, (2020) [21] in which they studied 12 nerves diagnosed as complete nerve injuries with the use of EDX, but using US, only three nerves showed fascicular continuity. Lauretti L, et al, [22] found that complete anatomical nerve interruption is easily recognized by the US, while internal nerve damage with the epineurium in continuity is more difficult to interpret.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 48 patients had associated fibrosis. These findings almost paralleled those of the study by Elfayoumy [ 14 ], who divided high-resolution US findings into three groups: fusiform in shape (increased CSA) (36.7%), fibrosis (36.7%), and neuroma (26.6%).…”
Section: Discussionsupporting
confidence: 84%
“…In the current study, the most common cause of PNI was crush injury and cut wounds in 54 of 69 cases, followed by the other types of injuries. In contrast, Uzun [ 8 ] and Elfayoumy [ 14 ] reported that cut injury by sharp objects was the most common cause of PNI. The site of laterality of the injured nerves in our study was more often on the left side (71.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Another disadvantage of electrodiagnostic studies is that, although accurate in their assessment of specific nerve involvement, they are often unable to distinguish axonotmesis from neurotmesis and they are unable to precisely localize a lesion which can be especially problematic in cases of multiple injury sites, entry points, ballistics, and shrapnel. 5,13 Furthermore, relying on electrodiagnostic testing can make for a conservative and lengthy management plan. Conservative management is not uncommon in PNI as injured nerves undergo a complex physiologic process known as Wallerian degeneration before regrowth begins.…”
Section: Discussionmentioning
confidence: 99%
“…Sonography is limited in its ability to visualize individual axons, myelin, and endoneurium. 11,12 However, advances in resolution have allowed for visualization of individual fascicles, perineurium, and epineurium (see Figure 4). Changes in echogenicity of nerve connective tissue, disruption of normal shape and cross-section areas of the nerve, interruption, and discontinuity of fascicles and/or the epineurium, swelling of retracted ends, and presence of intraneural bleeding can all indicate PNI and help to determine injury classification.…”
Section: Discussionmentioning
confidence: 99%